Taming the IoT: Operationalized Testing to Secure Connected Devices. - Pering, Trevor; Farrington, Kathy; Dahm, Thorsten (Computer (00189162), 2018)
Operationalized testing of built-environment IoT infrastructure is a key aspect of fostering security and development best practices. End-to-end automation can normalize the ecosystem and increase the velocity of system improvements and updates.